EquCab_Finn: A new reference genome assembly for the domestic horse, Finnhorse - Pokharel, Kisun; Weldenegodguad, Melak; Reilas, Tiina; Kantanen, Juha (Wiley-Blackwell, 2024)
Finnhorse is Finland's native and national horse breed and it has genetic affinities to northern European and Asian horses. It has historical importance for agriculture, forest work and transport and as a war horse. Finnhorse has four breeding sections in the studbook and is under conservation and characterisation efforts. We sequenced and annotated the genome of a Finnhorse mare from the working horse section using PacBio and Omni-C data. This genome can complement the existing Thoroughbred reference genome (EquCab 3.0) and facilitate genetic studies of horses from northern Eurasia. We assembled 2.4 Gb of the genome with an N50 scaffold length of 83.8 Mb and the genome annotation resulted in a total of 19 748 protein coding genes of which 1200 were Finnhorse specific. The assembly has high quality and synteny with the current horse reference genome. We manually curated five genes of interest and deposited the final assembly in the European Nucleotide Archive under the accession no. PRJEB71364.
Keywords: suomenhevonen; perimä; Finnhorse; genome